Leucine-Rich α-2-Glycoprotein 1 Suppresses Endothelial Cell Activation Through ADAM10-Mediated Shedding of TNF-α Receptor - Pang, Kuin Tian; Ghim, Mean; Liu, Chenghao; Tay, Hui Min; Fhu, Chee Wai; Chia, Rui Ning; Qiu, Beiying; Sarathchandra, Padmini; Chester, Adrian H.; Yacoub, Magdi H.; Wilkinson, Fiona L.; Weston, Ria; et al. (Frontiers in Cell and Developmental Biology, 2021)
Elevated serum concentrations of leucine-rich α-2-glycoprotein (LRG1) have been reported in patients with inflammatory, autoimmune, and cardiovascular diseases. This study aims to investigate the role of LRG1 in endothelial activation. LRG1 in endothelial cells (ECs) of arteries and serum of patients with critical limb ischemia (CLI) were assessed by immunohistochemistry and ELISA, respectively. LRG1 expression in sheared and TNF-α-treated ECs was analysed. The mechanistic role of LRG1 in endothelial activation was studied in vitro. Plasma of 37-week-old Lrg1-/- mice was used to investigate causality between LRG1 and TNFR1 shedding. LRG1 expression was highly expressed in ECs of stenotic but not normal arteries. LRG1 concentrations in serum of patients with CLI were elevated compared to healthy controls. LRG1 expression was shear dependent. It could be induced by TNF-α, and the induction of its expression was mediated by NF-κB activation. LRG1 inhibited TNF-α-induced activation of NF-κB signaling, expression of VCAM-1 and ICAM-1, and monocyte capture, firm adhesion, and transendothelial migration. Mechanistically, LRG1 exerted its function by causing the shedding of TNFR1 via the ALK5-SMAD2 pathway and the subsequent activation of ADAM10. Consistent with this mechanism, LRG1 and sTNFR1 concentrations were correlated in the serum of CLI patients. Causality between LRG1 and TNFR1 shedding was established by showing that Lrg1-/- mice had lower plasma sTNFR1 concentrations than wild type mice. Our results demonstrate a novel role for LRG1 in endothelial activation and its potential therapeutic role in inflammatory diseases should be investigated further.